NUMERICAL MODELLING OF THE MORPHODYNAMICS OF THE PLOČE GRAVEL BEACH IN RIJEKA (Advances in Civil and Architectural Engineering, 2022)
The morphodynamics of an artificial gravel beach in the Bay of Rijeka (Ploče Beach) was analyzed. The morphological changes of the beach face were monitored through an intense situation of gravitational surface wind waves from the incident SSW direction. A numerical modeling technique was applied, after initially establishing a numerical model for wave deformation. A model for sediment transport was established based on its results. Both models were based on the finite volume method. In addition, the partial contribution of the longshore component of sediment transport was analyzed based on empirical formulae. The modeling results were verified by comparing the positions and amounts of eroded/accumulated material along the beach with the processing of terrain images in the form of point clouds. The erosion and accumulation positions of the beach sediment material, obtained by numerical model simulations, corresponded to the surveyed positions. The total volume of eroded and accumulated material based on terrain image processing corresponded to the model values.